Vesical Calculi in Children:Study of their Nutritional Status - Zein-el-Amir , Masroor Hussain Malik , Shazia Khan ,Fouzia Amir Khan ,Ashfaq Ahmed , Muhammad Afzal Farooqi (Journal of Rawalpindi Medical College, 2012)
Background: To evaluate the nutritional status of children with bladder stones as a possible etiology of so called primary or endemic bladder calculi. Methods: In this descriptive study 52 children having bladder stones were enrolled according to specified criteria. Nutritional status was assessed according to weight for height or length deficit. Nutritional status assessment was carried out according to weight for height or length deficit, taking standard deviation to classify mild, moderate and severe malnutrition, corresponding to - 1 Z-score, -2 Z or -3 Z-score with National centre for Health Statistics (NCHS). Results: Of the total 187 paediatric admissions,number of children with vesical calculi was 52 (27.8%). Malnutrition was detected in 57.6%. Nutritional deficiencies were found in 25 patients (83.3%) with idiopathic stone disease.Three patients (10%) revealed anatomical abnormalities, 01 patient (3.3%) had metabolic and 01 patient (3.3%) had associated neurological abnormalities. Conclusion: Imbalanced nutrition is the principal risk factor for paediatric bladder calculi.